Carbon nanotube wafer film transmission electron microscope sample preparation method
By coating the polymer support layer on the surface of the carbon nanotube film and etching the silica layer with a selective etching liquid, the problem of difficult to maintain structural integrity and surface morphology information during the preparation process is successfully solved. , improves sample preparation efficiency and success rate, and realizes efficient planar TEM observation of carbon nanotubes.
Patent Information
- Application Number
- CN202411650261.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, when preparing carbon nanotube wafer thin-film transmission electron microscope samples, it is difficult to maintain the structural integrity and surface morphology information of carbon nanotubes, and there is a lack of reliable separation and transfer methods, resulting in low sample preparation efficiency and low success rate.
The polymer support layer is coated on the surface of the carbon nanotube film, and the silicon dioxide layer is etched using a selective etching liquid, so that the polymer support layer and the carbon nanotube film are separated from the silicon substrate, and then transferred to the carrier and removed the support. The layer is dried to avoid deformation of the film.
Complete separation and transfer of carbon nanotube films is achieved, deformation caused by mechanical damage and surface tension is avoided, sample preparation efficiency and success rate are improved, and plane TEM observation of carbon nanotubes is possible.
Smart Images

Figure CN119224022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor material characterization, and in particular to a carbon nanotube wafer film transmission electron microscope sample preparation method. Background Art
[0002] Carbon nanotubes have important application prospects in the fields of microelectronics, sensors, energy, etc. due to their unique one-dimensional structure and excellent performance. In practical applications, carbon nanotubes are usually grown on the surface of a silicon wafer with a silicon dioxide layer to form a composite structure. A silicon wafer is used as a substrate, and a 200-300nm thick silicon dioxide layer is first deposited on it, and then a carbon nanotube film (thickness 2-4nm, tube diameter 1.2-1.7nm) is grown on the silicon dioxide layer.
[0003] Transmission electron microscopy (TEM) is a key tool for characterizing the structure and properties of carbon nanotubes; however, existing technologies have the following serious problems when preparing such samples: 1) Currently, carbon nanotube cross-section samples are mainly prepared by focused ion beam (FIB), which can only observe the cross section of the carbon nanotubes and cannot obtain the surface morphology information of the carbon nanotubes; 2) Since carbon nanotubes are tightly bound to the silicon dioxide layer, it is difficult to separate them completely to prepare planar TEM samples; 3) When traditional mechanical thinning or chemical stripping methods are used to separate carbon nanotubes from the silicon dioxide layer, the structural integrity of the carbon nanotubes may be destroyed; 4) There is still a lack of reliable methods to separate ultra-thin carbon nanotube films from the silicon dioxide surface and transfer them to the TEM sample grid.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon nanotube wafer film transmission electron microscope sample preparation method, which can achieve complete separation of the carbon nanotube film on the basis of maintaining the original structure and performance of the carbon nanotube.
[0006] The present invention provides a method for preparing a carbon nanotube wafer film transmission electron microscope sample, comprising the following steps:
[0007] S1: growing a silicon dioxide layer and a carbon nanotube film on the surface of a silicon substrate in sequence, and coating a polymer solution on the surface of the carbon nanotube film to form a polymer support layer;
[0008] S2: etching the silicon dioxide layer using a selective etching solution, so that the composite film of the polymer support layer and the carbon nanotube film is separated from the silicon substrate;
[0009] S3: transferring the detached composite film to a carrier, drying it, and then removing the polymer support layer.
[0010] In step S1, the silicon substrate is a 4-inch P-type silicon wafer, a 6-inch N-type silicon wafer, etc.; the thickness of the silicon dioxide layer is 200-300nm; the thickness of the carbon nanotube film is 2.5-3.5nm, and the diameter of the carbon nanotube is 1.3-1.7nm.
[0011] Before coating the polymer solution, the silicon substrate on which the carbon nanotube film is grown is cut into small pieces of appropriate size and cleaned using an ultrasonic cleaner or a plasma cleaner to remove possible contaminants.
[0012] The polymer solution may be a polymethyl methacrylate (PMMA) solution, a polyimide (PI) solution, etc. The mass concentration of the polymethyl methacrylate solution may be 3-5%, such as 4%, and the molecular weight of the polymethyl methacrylate may be 900-1000K, such as 950K. The concentration of the PMMA solution has a significant effect on the transfer effect. If the concentration is too low, it will lead to insufficient support, and if the concentration is too high, it will be difficult to remove later. The mass concentration of the polyimide solution is 14-16%, such as 15%. The polyimide support layer formed by the polyimide solution can provide better mechanical strength.
[0013] The coating can be done by spin coating or spray coating. The appropriate coating method can be selected according to the polymer solution. For example, polymethyl methacrylate solution can be spin coated, and polyimide solution can be spray coated. The rotation speed during spin coating is 2000-4000r / min, for example, 3000r / min, and the time is 30-90s, for example, 60s; after spin coating, it is dried at 80-100°C for 3-7min to fully cure the polymethyl methacrylate. The speed during spray coating is 0.4-0.6mL / min, for example, 0.5mL / min; the substrate temperature is 55-65°C, for example, 60°C; after spray coating, it is annealed at 110-130°C in a nitrogen atmosphere for 50-70min to fully cure the polyimide.
[0014] In step S2, the selective etching solution can be a first mixed solution or a second mixed solution; wherein the first mixed solution is a mixed solution of NH4F solution and HF solution, the NH4F solution can be a 40% NH4F aqueous solution, the HF solution can be a 49% HF aqueous solution, and the volume ratio of the NH4F solution to the HF solution in the first mixed solution is (5-7):1, for example, 6:1; the second mixed solution is a mixed solution of hydrofluoric acid solution and glacial acetic acid solution, the hydrofluoric acid solution can be a 40% HF aqueous solution, and the volume ratio of the hydrofluoric acid solution to the glacial acetic acid solution in the second mixed solution is (0.8-1.2):1, for example, 1:1.
[0015] When the first mixed solution is used to etch the silicon dioxide layer, the etching temperature is 20-30°C, and there is no strict limit on the etching time. The etching time can be adjusted according to the actual thickness of the silicon dioxide. The etching is terminated when the composite film begins to separate from the silicon substrate. The etching time is, for example, 10-15 minutes. When the second mixed solution is used to etch the silicon dioxide layer, the etching temperature is -4°C to -6°C, and the etching time is 5-10 minutes. Low-temperature etching reduces chemical damage to the carbon nanotubes.
[0016] In step S3, transferring the detached composite film to a carrier includes: transferring the detached composite film to a deionized water surface, then transferring the composite film floating on the deionized water surface to a transmission electron microscope sample grid, and then naturally drying for 15-45 minutes; or, transferring the detached composite film to a methanol solution, then transferring the composite film immersed in the methanol solution to a pre-cooled sample rack. Folding of the composite film should be avoided during the transfer process.
[0017] Drying can be carried out by critical point drying or freeze drying; wherein, critical point drying uses liquid CO2 at 30-32°C, 7.0-7.5MPa, and the drying time is 30-60min. During the critical point drying process, the rate of heating and pressure release should be kept slow and uniform; the initial temperature during freeze drying is -80°C, the heating rate is 4-6°C / h, and the drying time is 10-15h. Freeze drying avoids surface tension and is particularly suitable for large area samples.
[0018] According to the material of the polymer support layer, the polymer support layer is removed by solvent treatment or heat treatment. Specifically; the polymer support layer is removed by solvent treatment, including: immersing the composite film in an acetonitrile solution for 2-4 hours, then rinsing with isopropanol 2-4 times, each time for 1-2 minutes, and then drying in a vacuum environment at 35-45°C for 0.5-2 hours. The polymer support layer is removed by heat treatment; the heat treatment is carried out in an argon atmosphere, the heating rate is 8-12°C / min, the heat treatment temperature is 400-500°C, and the heat treatment time is 1.5-2.5 hours. Removing the polymer support layer by heat treatment is beneficial to avoid solvent residue.
[0019] After removing the polymer support layer, the following quality verification steps are also included:
[0020] The integrity of the carbon nanotube film was observed using scanning electron microscopy;
[0021] Raman spectroscopy was used to characterize the structure of carbon nanotubes.
[0022] The implementation of the present invention has at least the following advantages:
[0023] 1. The present invention provides mechanical strength for the carbon nanotube film by preparing a polymer support layer on the surface of the carbon nanotube film, which can prevent the carbon nanotube film from being damaged during the transfer process; at the same time, the silicon dioxide layer is etched using a selective etching solution to ensure the complete separation of the carbon nanotubes and silicon dioxide, thereby achieving the complete transfer of the carbon nanotube film.
[0024] 2. The present invention has no mechanical force in the whole process, thus avoiding mechanical damage; at the same time, the detached composite film is transferred to a carrier and then dried, thus avoiding film deformation caused by surface tension and maintaining the original structure of the carbon nanotubes.
[0025] 3. The entire preparation process of the present invention can be completed within 2-3 hours, with a success rate of more than 80%, which improves the sample preparation efficiency and preparation success rate, makes planar TEM observation of carbon nanotube films possible, and provides a new research method for the structural characterization of carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a high-magnification SEM image of the original carbon nanotube film before transfer;
[0028] Figure 2 is the Raman spectrum of the original carbon nanotube film before transfer;
[0029] Figure 3 This is a high-magnification SEM image of the carbon nanotube film prepared in Example 1;
[0030] Figure 4 This is a Raman spectrum of the carbon nanotube film prepared in Example 1;
[0031] Figure 5 This is a high-magnification SEM image of the carbon nanotube film prepared in Example 2;
[0032] Figure 6 This is a Raman spectrum of the carbon nanotube film prepared in Example 2;
[0033] Figure 7 A high-magnification SEM image of the carbon nanotube film prepared in Comparative Example 1;
[0034] Figure 8 The Raman spectrum of the carbon nanotube film prepared in Comparative Example 1;
[0035] Fig. 9 This is a high-magnification SEM image of the carbon nanotube film prepared in Control Example 2. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] The carbon nanotube wafer thin film transmission electron microscope sample preparation method of this embodiment includes the following steps:
[0041] 1. Sample pretreatment
[0042] The silicon substrate sample of this embodiment is a 4-inch P-type silicon wafer with a 200 nm thick silicon dioxide layer. A 2.5 nm thick carbon nanotube film is grown on the surface of the silicon dioxide layer, and the diameter of the carbon nanotube is 1.4±0.2 nm.
[0043] The silicon wafer was cut into 5 mm × 5 mm pieces using a diamond cutting pen. The cut samples were placed in an ultrasonic cleaner and cleaned with acetone and isopropanol for 5 min each, and then the sample surface was dried with a nitrogen stream.
[0044] 2. Preparation of PMMA support layer
[0045] PMMA (molecular weight 950K) was dissolved in styrene to prepare a PMMA solution with a mass content of 4 wt%.
[0046] Place the pretreated sample on the rotating table of the coating machine and adjust the speed to 3000r / min; use a micropipette to draw 100μL of PMMA solution, slowly drip it on the center of the sample, and spin coat for 60s. Then, transfer the sample to a 90℃ hot plate and heat it for 5min to completely cure the PMMA and form a PMMA support layer on the surface of the carbon nanotube film.
[0047] 3. Selective etching
[0048] Prepare BOE solution in a fume hood. The BOE solution is prepared by mixing 40% NH4F aqueous solution and 49% HF aqueous solution in a volume ratio of 6:1. Use a constant temperature water bath to control the temperature of the BOE solution at 25±1°C.
[0049] Use Teflon tweezers to hold the sample and slowly immerse it in BOE solution for selective etching; observe the sample, and when the edge of the PMMA support layer begins to slightly lift up (about 12 minutes), immediately transfer the sample to deionized water. Gently shake the sample in deionized water to completely separate the composite film of the PMMA support layer and the carbon nanotube film from the silicon substrate.
[0050] 4. Sample transfer
[0051] Prepare TEM copper grids (300 mesh standard copper microgrid).
[0052] The composite film floating in deionized water was transferred to a TEM copper grid, and the excess water around the TEM copper grid was gently absorbed using filter paper, followed by natural drying at room temperature for 30 min.
[0053] 5. Critical point drying
[0054] The sample was placed in the sample chamber of the critical point dryer and liquid CO2 was injected to replace the water in the sample for 40 minutes.
[0055] The sample chamber was sealed, the temperature was raised to 31.1°C, the pressure automatically rose to 7.38MPa, and this state was maintained for 15 minutes; then, CO2 was slowly released (release rate was about 0.5MPa / min) until normal pressure was restored.
[0056] 6. Remove the PMMA support layer
[0057] Immerse the sample in 40 mL of acetonitrile solution and soak it at room temperature for 2 hours. Then, take out the sample and rinse it with fresh isopropanol three times, 1 minute each time. Dry the sample in a vacuum oven at 40°C for 1 hour.
[0058] 7. Quality Verification
[0059] The samples were observed using a scanning electron microscope at an accelerating voltage of 5 kV to check the integrity of the carbon nanotube film and to confirm that there were no obvious wrinkles or damages.
[0060] Raman spectrometer was used for characterization: laser wavelength: 532 nm; power: less than 1 mW (to avoid damaging the sample); acquisition time: 60 s; confirm the G peak (~1590 cm -1 ) and 2D peak (~2700cm -1 )’s position and intensity ratio.
[0061] The results are as follows:
[0062] Success rate: 20 experiments were repeated according to the above method, and samples that can be used for TEM observation were successfully obtained 18 times, with a success rate of 90%.
[0063] Sample quality:
[0064] Combination Figure 1 , Figure 3 As shown, scanning electron microscope observation shows that the carbon nanotube film prepared in this embodiment is continuous and complete, without obvious wrinkles or damage defects.
[0065] Combination Figure 2 , Figure 4 As shown, the Raman spectrum shows that the ratio of the G peak to the D peak of the original carbon nanotubes before transfer is about 95.9 (the larger the ratio, the better the preservation of the carbon nanotubes, and the maximum value is 100); the position and intensity of the characteristic peaks of the carbon nanotubes after transfer are basically consistent with those before transfer, and the ratio of the G peak to the D peak is about 95.8, proving that the structure of the carbon nanotubes after transfer is not damaged.
[0066] Time efficiency: The entire preparation process can be completed within 4 h.
[0067] Example 2
[0068] The carbon nanotube wafer thin film transmission electron microscope sample preparation method of this embodiment includes the following steps:
[0069] 1. Sample pretreatment
[0070] The silicon substrate sample of this embodiment is a 6-inch N-type silicon wafer with a 300 nm thick silicon dioxide layer. A 3.5 nm thick carbon nanotube film is grown on the surface of the silicon dioxide layer, and the diameter of the carbon nanotube is 1.6±0.1 nm.
[0071] The sample surface was treated using a plasma cleaning machine with the following parameters: gas: oxygen; power: 50 W; time: 30 s; the silicon wafer was cut into small pieces of 4 mm×4 mm.
[0072] 2. Preparation of PI support layer
[0073] A PI solution with a mass content of 15 wt% was sprayed on the surface of the sample using a spraying system, and the spraying parameters were as follows: nozzle height: 10 cm; spraying rate: 0.5 mL / min; substrate temperature: 60°C.
[0074] Annealing was performed at 120° C. for 1 h in a nitrogen atmosphere to fully solidify the PI and form a PI support layer on the surface of the carbon nanotube film.
[0075] 3. Selective etching
[0076] A 40% hydrofluoric acid solution and a glacial acetic acid solution were uniformly mixed in a volume ratio of 1:1 to prepare a selective etching solution, which was pre-cooled for later use.
[0077] Selective etching was performed at a low temperature of -5°C (using an ice bath): the sample was immersed in the pre-cooled selective etching solution for about 8 minutes.
[0078] The sample was rinsed with a large amount of deionized water to terminate the etching reaction; then, the sample was transferred to a methanol solution to replace the deionized water.
[0079] 4. Freeze drying transfer
[0080] The sample immersed in the methanol solution was quickly transferred to a sample rack precooled at -80°C, and then the sample rack was placed in a freeze dryer for freeze drying. The parameters were as follows: initial temperature: -80°C; vacuum degree: 0.1 Pa; heating rate: 5°C / h; total drying time: 12h.
[0081] The composite film of the dried PI support layer and the carbon nanotube film was transferred onto a titanium grid (400 mesh titanium grid microgrid) using an electrostatic adsorber.
[0082] 5. Remove the PI support layer
[0083] The sample was placed in a tubular furnace and heat treated in an argon atmosphere; the parameters were as follows: heating rate: 10°C / min; final temperature: 450°C; holding time: 2h; and naturally cooled to room temperature.
[0084] 6. Characterization and analysis
[0085] X-ray photoelectron spectroscopy (XPS) analysis was performed with the following parameters: excitation source: monochromatic Al Kα ray; power: 150 W; analysis range: 400 μm × 400 μm; and confirmation that the PI support layer had been completely removed.
[0086] The distribution and integrity of the carbon nanotubes were confirmed by using TEM at an accelerating voltage of 80 kV.
[0087] Sample quality:
[0088] Combination Figure 1 , Figure 5 As shown, scanning electron microscope observation shows that the carbon nanotube film prepared in this embodiment is continuous and complete, without obvious wrinkles or damage defects.
[0089] Combination Figure 2 , Figure 6 As shown, the Raman spectrum shows that the characteristic peak position and intensity of the carbon nanotubes prepared in this example are basically consistent with those before transfer, and the ratio of the G peak to the D peak is about 95.8, proving that the structure of the carbon nanotubes is not damaged after transfer.
[0090] This embodiment is particularly suitable for situations where extremely high requirements are placed on the sample surface morphology, carbon nanotube films that need to be transferred over a large area, and research that is particularly sensitive to chemical contamination.
[0091] Comparative Example 1
[0092] This comparative example uses a conventional mechanical thinning method to separate the carbon nanotubes and the silicon dioxide layer.
[0093] Combination Figure 1 , Figure 7 As shown, scanning electron microscope observation shows that the carbon nanotubes prepared in this control example are largely broken and twisted, and have obvious defects such as wrinkles or damage.
[0094] Combination Figure 2 , Figure 8 As shown, the Raman spectrum shows that the characteristic peak position and intensity of the carbon nanotubes prepared in this control example are significantly changed compared with those before transfer, and the ratio of the G peak to the D peak is about 50.5, proving that the structure of the carbon nanotubes is destroyed after transfer.
[0095] Comparative Example 2
[0096] This comparative example uses a conventional chemical stripping method to separate the carbon nanotubes from the silicon dioxide layer.
[0097] Combination Figure 1 , Fig. 9 As shown, when hydrofluoric acid (HF) is used for chemical stripping, the reaction process is difficult to control precisely, which can easily cause excessive corrosion; scanning electron microscopy observations show that the structure of the carbon nanotubes prepared in this control example is damaged, which significantly changes the electrical and physical properties of the carbon nanotubes.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing carbon nanotube wafer thin film transmission electron microscopy samples, characterized in that: The steps include: S1: growing a silicon dioxide layer and a carbon nanotube film on the surface of a silicon substrate in sequence, and coating a polymer solution on the surface of the carbon nanotube film to form a polymer support layer; S2: etching the silicon dioxide layer using a selective etching solution, so that the composite film of the polymer support layer and the carbon nanotube film is separated from the silicon substrate; S3: transferring the detached composite film to a carrier, drying it, and then removing the polymer support layer.
2. The method for preparing carbon nanotube wafer thin film transmission electron microscope samples according to claim 1, characterized in that: The polymer solution is a polymethyl methacrylate solution or a polyimide solution. The mass concentration of the polymethyl methacrylate solution is 3-5%, and the mass concentration of the polyimide solution is 14-16%.
3. The method for preparing carbon nanotube wafer thin film transmission electron microscope samples according to claim 1, characterized in that: The coating is performed by spin coating or spray coating; wherein the rotation speed during spin coating is 2000-4000r / min, the time is 30-90s, and after spin coating, it is dried at 80-100°C for 3-7min; the speed during spray coating is 0.4-0.6mL / min, the substrate temperature is 55-65°C, and after spraying, it is annealed at 110-130°C in a nitrogen atmosphere for 50-70min.
4. The method for preparing carbon nanotube wafer thin film for transmission electron microscopy according to claim 1, characterized in that: The selective etching solution is a first mixed solution or a second mixed solution; wherein the first mixed solution is a mixed solution of NH4F solution and HF solution, and the volume ratio of NH4F solution to HF solution in the first mixed solution is (5-7):1; the second mixed solution is a mixed solution of hydrofluoric acid solution and glacial acetic acid solution, and the volume ratio of hydrofluoric acid solution to glacial acetic acid solution in the second mixed solution is (0.8-1.2):
1.
5. The method for preparing carbon nanotube wafer thin film for transmission electron microscopy according to claim 4, characterized in that: When the first mixed solution is used to etch the silicon dioxide layer, the etching temperature is 20-30° C. and the etching time is 10-15 min. When the second mixed solution is used to etch the silicon dioxide layer, the etching temperature is -4° C. to -6° C. and the etching time is 5-10 min.
6. The method for preparing carbon nanotube wafer thin film for transmission electron microscopy according to claim 1, characterized in that: Transferring the released composite film to a carrier includes: The detached composite film is transferred to the surface of deionized water, and then the composite film floating on the surface of deionized water is transferred to the transmission electron microscope sample grid, and then naturally dried for 15-45 minutes; alternatively, the detached composite film is transferred to a methanol solution, and then the composite film immersed in the methanol solution is transferred to a pre-cooled sample rack.
7. The method for preparing carbon nanotube wafer thin film for transmission electron microscopy according to claim 1, characterized in that: The drying is critical point drying or freeze drying; wherein, the critical point drying is carried out using liquid CO2 at 30-32°C and 7.0-7.5MPa, and the drying time is 30-60min; the initial temperature during freeze drying is -80°C, the heating rate is 4-6°C / h, and the drying time is 10-15h.
8. The method for preparing carbon nanotube wafer thin film for transmission electron microscopy according to claim 1, characterized in that: The polymer support layer is removed by solvent treatment, including: immersing the composite film in an acetonitrile solution for 2-4 hours, then rinsing with isopropanol 2-4 times, each time for 1-2 minutes, and then drying in a vacuum environment at 35-45° C. for 0.5-2 hours.
9. The method for preparing carbon nanotube wafer thin film for transmission electron microscopy according to claim 1, characterized in that: The polymer support layer is removed by heat treatment; the heat treatment is carried out in an argon atmosphere, with a heating rate of 8-12°C / min, a heat treatment temperature of 400-500°C, and a heat treatment time of 1.5-2.5h.
10. The method for preparing carbon nanotube wafer thin film for transmission electron microscopy according to claim 1, characterized in that: After removing the polymer support layer, the following quality verification steps are also included: The integrity of the carbon nanotube film was observed using scanning electron microscopy; Raman spectroscopy was used to characterize the structure of carbon nanotubes.